Dispositions, capacités et pratiques de SST dans les petites entreprises : opinions de patrons, d’employés et d’intervenants en SST au Québec - Danièle Champoux; Jean-Pierre Brun (Perspectives Interdisciplinaires sur le Travail et la Santé)
The state of OHS in small businesses (SB) is not formally documented in Québec due to the lack of OHS statistics based on company size. OHS practitioners, however, report that workers are exposed to major and poorly controlled hazards. Interviews with employers and employees in six manufacturing SBs and with outside OHS practitioners are used to describe and explain prevention practices in relation to the two main means of prevention in the legislation (AOHS). OHS practitioners observe that the practices relating to employee participation and risk prevention at source do not correspond to the legislation’s objectives. The results question the adaptation of Québec’s OHS system to the needs of SBs.